2019
DOI: 10.1002/ejp.1348
|View full text |Cite
|
Sign up to set email alerts
|

What do you expect? Catastrophizing mediates associations between expectancies and pain‐facilitatory processes

Abstract: Background Pain expectancies are associated with altered pain sensitivity in individuals with chronic pain. However, little is known about the processes by which pain expectancies impact pain processing. This study assessed the association between pain expectancies and temporal summation (TS) of pain, and examined whether pain catastrophizing mediated this association. Methods In this cross‐sectional study, participants (437 chronic low back pain [CLBP] patients, 115 controls) completed self‐report measures of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 81 publications
1
11
3
Order By: Relevance
“…9,50,63 Contrastingly, previous studies report psychological status (self-reports and experimental induction of acute stress) negatively influence the CPM effect in healthy and symptomatic individuals. 8,23,26,27,50,86 However, adjusting for the PCS-helplessness in this study did not significantly influence the variance of PA or SB on CPM effects. Since participants in this study had lower scores in PCS and other psychological attributes, the role of psychological confounding on the observed relationship cannot be entirely ruled out.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…9,50,63 Contrastingly, previous studies report psychological status (self-reports and experimental induction of acute stress) negatively influence the CPM effect in healthy and symptomatic individuals. 8,23,26,27,50,86 However, adjusting for the PCS-helplessness in this study did not significantly influence the variance of PA or SB on CPM effects. Since participants in this study had lower scores in PCS and other psychological attributes, the role of psychological confounding on the observed relationship cannot be entirely ruled out.…”
Section: Discussioncontrasting
confidence: 60%
“…11,28 This perceptual component is supported by our data showing significant positive correlations between MTS scores, PCS scores, and pain severity/interference. 8,16,65,66 Thus, peripheral mechanisms of TS and perceptions might have confounded the relationship between PA/SB and MTS scores.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have investigated pathways among smaller numbers of contextual variables and suggested, for example, that self-efficacy mediates the impact on osteoarthritis pain of practitioners communicating positive expectancies, 35 affective aspects of the therapeutic relationship may shape Open access patient expectancies in chronic pain, 70 and expectancies might impact pain via reduced catastrophising in chronic back pain. 33 The current results further suggest contextual factors reduce back-related disability in part by enhancing patient self-efficacy for coping with pain, reducing the perceived threat of pain and reducing psychosocial distress. This is broadly consistent with the fear avoidance model 34 and social cognitive theory.…”
Section: Discussionsupporting
confidence: 53%
“…Such components include: positive and empathetic patient-practitioner relationships and a strong patient-practitioner alliance [4][5][6][7][8][9][10] (patient-practitioner relationship); patients' outcome expectancies and perceived treatment credibility 9 11-16 (patient beliefs); musculoskeletal practitioners' beliefs about pain [17][18][19][20][21][22] and outcome expectancies 23 (practitioner beliefs); good organisational environments (eg, collegiality) 24 , the physical-sensory environment (eg, music) 25 and the healthcare sector [26][27][28] (environment), although evidence of effects of healthcare sector on patient outcomes is mainly qualitative. Contextual components might impact patient outcomes via (1) behavioural pathways (eg, improved self-management), 29 30 but see also Haanstra et al who found that adherence accounted for only a small proportion of the relationship between expectancies and pain outcomes, 31 (2) psychosocial pathways (eg, reconceptualising pain as less threatening [32][33][34] ; increased selfefficacy 35 36 ) and/or (3) neurophysiological pathways. [37][38][39][40][41] The focus in this study was on psychosocial pathways; more details on how these were hypothesised to operate are provided in our published protocol.…”
Section: Introductionmentioning
confidence: 99%
“…It is well established that pain catastrophizing (PC) is associated with pain severity and interference (Quartana, Campbell, & Edwards, ). There is also evidence from accident victims that catastrophizing, and PC in particular, mediates the relationship between pain intensity and PTSD (Andersen, Karstoft, Brink, & Elklit, ; Carriere, Martel, Meints, Cornelius, & Edwards, ; Pedler, Kamper, & Sterling, ). TRBs can be viewed as a form of catastrophizing, and are associated with higher levels of PTSD, comorbidity and functional impairment in trauma‐exposed individuals (Heron‐Delaney, Kenardy, Charlton, & Matsuoka, ; Ozer, Best, Lipsey, & Weiss, ).…”
Section: Introductionmentioning
confidence: 99%